Pemanfaatan Sistem Bio-Cycle Farming dalam Penanganan Limbah Rumah Tangga untuk Peningkatan Pendapatan Petani - Andi Lelanovita Sardianti; Risna Nona; Fahrizal; Muhamad Yazid Bustomi; Zainal Abidin; Wardatul Hidayah (Jurnal Galung Tropika, 2025)
The bio-cycle farming system is intended to introduce the community to business-oriented and environmentally friendly agricultural businesses. The integrated biological cycle of agriculture, in which all components are helpful, and no waste is wasted or thrown away, reduces the risk of crop failure because dependence on a commodity can be avoided and saves production costs. This study aims to determine the effect of utilizing the bio-cycle farming system in handling household waste. Data collection used a survey method with a sample of 33 people. Quantitative data were analyzed using validity tests, reliability tests, Kolmogorov-Smirnov classical assumption tests, simple regression tests, and hypothesis testing, namely the t-test and the coefficient of determination (R2). The results showed that the utilization of the bio-cycle farming system had a significant effect on handling household waste. The variable utilization of the bio-cycle farming system (X) showed a calculated t value greater than the t table (5.955> t table 2.040) or sig <? (0.000 <0.05). Meanwhile, the variation in changes in the waste management variable (Y) is influenced by changes in the independent variable consisting of the use of the bio cycle farming system (X) by 53.4%. In comparison, other factors outside this research influence the remaining 46.6%.